Healthy vision : prevent and reverse eye disease through better nutrition - Adams, Neal. frey50 (Guilford, Connecticut Lyons Press, 2014)
The first mainstream book to explore the clinically proven link between eating nutrient-rich foods and eye health, explaining how readers can maintain vision well into old age, alleviate eye conditions, and even reverse the progress of diseases, without a prescription or surgery, by eating a specific nutrient-rich diet.
Keywords: Eye -- Diseases -- Prevention; Eye -- Diseases -- Nutritional aspects; Eye Diseases -- prevention & control; Nutrition Therapy; Medical / Ophthalmology; Popular works